Assessing the Impact of Structural Adjustmenton the Poor : The Case of Malawi - Brekk, Odd (IMF Working Papers; Working Paper ;, 1991)
This paper applies, through a case study on Malawi, a simple methodology indicating the first-round (i.e., price) effects of macroeconomic policies on real earnings of the poor. As the economic program in Malawi has not involved substantial exchange rate action or cuts in subsidies, the real incomes of the poor have been most clearly affected by the pricing policies of the agricultural parastatal and the overall anti-inflationary measures incorporated in the program; developments in minimum wages have also been important. The study suggests that, on balance, these various factors have led to an increase in real incomes of the poor over the program period.